Acute antibody-mediated rejection of renal transplant associated with cellular crescents: First case report - Andrade, Luís Gustavo Modelli de [UNESP]; Viero, Rosa Marlene [UNESP]; Carvalho, M. F C [UNESP] (Elsevier, 2011)
Acute antibody-mediated rejection is characterized by histological abnormalities such as glomerulitis, capillaritis, or thrombosis associated with presence of C4d and specific anti-donor antibodies. Reports on the association of glomerular injuries with cellular crescents in antibody-mediated rejection are not found in the literature. We report a unique case of antibody-mediated rejection associated with cellular crescents and suggest that such histological abnormality should be considered in the differential diagnosis of acute antibody-mediated rejection. © 2011 Elsevier Inc.
Keywords: mycophenolic acid; prednisone; tacrolimus; thymocyte antibody; acute antibody mediated rejection; acute graft rejection; adult; case report; differential diagnosis; female; focal glomerulonephritis; glomerulitis; human; immunosuppressive treatment; inflammatory infiltrate; kidney graft; priority journal; Female; Graft Rejection; Humans; Kidney Transplantation; Middle Aged